Development Of Broodstock Maturation Feed With Supplementation Of Arachidonic Acid (Ara, 20:4n-6) And Docosahexaenoic Acid (Dha, 22:6n-3) For Female Giant Freshwater Prawn, Macrobrachium Rosenbergii - Ibrahim, Saadiah (2023)
The giant freshwater prawn (GFP), Macrobrachium rosenbergii (de Man, 1879), is one of the important commodities in Malaysia's aquaculture industry. The main challenge in Macrobrachium farming is the supply of high-quality seeds, which has become an increasingly critical issue. To address this problem, a study was conducted to investigate the effects of feeding maturation diets containing arachidonic acid (ARA, 20:4n-6) and docosahexaenoic acid (DHA, 22:6n-3) at optimal levels on the maturation and breeding performance of female M. rosenbergii. The research aimed to evaluate the impact of maturation diets enriched with ARA and DHA on the maturation of female GFP, including assessments of gonad development, egg quality, larval quantity, and oocyte size. The analysis also included the examination of fatty acid content in the shrimp's body. The study employed different formulations of maturation diets with varying ARA and DHA levels, comparing them with a control diet. Parameters studied in the female GFP given the experimental diets included reproductive effort, egg quality, larval yield, gonad and hepatopancreas histology, and fatty acid content in the study samples. Three feeding trial experiments were conducted to develop the maturation diets for female M. rosenbergii. The first experiment examined the effects of different diet forms and moisture content on the reproductive performance of female M. rosenbergii. The second experiment aimed to determine the optimal dietary ARA level for enhanced reproductive performance of female GFP